Reliability Analysis of Bifacial PV Panel-Based Inverters Considering the Effect of Geographical Location - Sainadh Singh Kshatri; Javed Dhillon; Sachin Mishra; Rizwan Tariq; Naveen Kumar Sharma; Mohit Bajaj; Ateeq Ur Rehman; Muhammad Shafiq; Jin-Ghoo Choi (Energies, 2021)
Recent trends in the photovoltaic (PV) technology industry are moving towards utilizing bifacial PV panels. Unlike traditional PV panels, bifacial PV panels can yield energy from both sides of the panel. Manufacturers specify that bifacial PV panels can harness up to 30% more energy than traditional PV panels. Hence, bifacial PV panels are becoming a common approach at low solar irradiance conditions to yield more energy. However, a bifacial PV panel increases PV inverter loading. The PV inverter is the most unreliable component in the entire PV system. This results in a negative impact on PV system reliability and cost. Hence, it is necessary to anticipate the inverter’s reliability when used in bifacial PV panels. This paper analyzes the reliability, i.e., lifetime, of PV inverters, considering both monofacial and bifacial PV panels for the analysis. Results showed that the increase in bifacial energy yield could significantly affect PV inverter reliability performance, especially in locations where the average mission profile is relatively high.